Primary gastrointestinal aspergillosis: A case report and literature review - Ceylan, Bahadır; Yılmaz, Mesut; Beköz, Hüseyin Saffet; Ramadan, Saime; Ertan Akan, Gülhan; Mert, Ali (EDIMES Edizioni Medico Scientifiche, 2019)
Invasive aspergillosis is a severe infection that generally involves the lungs. Primary gastrointestinal aspergillosis is the least common form of invasive aspergillosis. A patient aged 65 years developed a febrile neutropenic episode following an autologous stem cell transplant for plasmacytoid variant diffuse large B-cell gastric non-Hodgkin’s lymphoma. He had abdominal pain on the second day of the febrile neutropenic episode and ileus occurred on the sixth day. His general condition deteriorated despite broad spectrum antibiotics and caspofungin treatment, and intestinal perforation occurred on the nineteenth day of the febrile neutropenic episode. Pathological examination of the resected jejunum and ileum revealed mould hyphae compatible with aspergillus. The patient died due to massive gastrointestinal bleeding on the fifth post-operative day. Although a rare condition, primary gastrointestinal aspergillosis should be kept in mind while treating neutropenic patients with gastrointestinal symptoms.
Keywords: Aspergillosis; Gastrointestinal Tract; Ileum; Jejunum